ICT Based-Problem Based Learning on Students' Cognitive Learning Outcomes - Enny Kristinawati; Herawati Susilo; Abdul Gofur (Universitas Negeri Malang, 2019)
Abstract: The purpose of this research is to determine the impact of Problem Based Learning through ICT on students' cognitive achievement. This research using a quasi-experiment design with nonequivalent control group design. Data of pretest and posttest were collected and analyzed by ANACOVA. The result showed that there are differences of cognitive achievement among students in the experimental class and in a conventional class. The average score of student's cognitive achievement in experimental class is 69.032 and in the conventional class is 62.078, which is mean that the achievement of cognitive on students that were taught by PBL through ICT is significantly higher than the students that were taught by conventional learning. Key Words: problem based learning, ICT, cognitive achievement Abstrak: Tujuan penelitian ini adalah untuk mengetahui pengaruh pembelajaran dengan model problem based learning berbasis TIK terhadap hasil belajar kognitif siswa. Jenis penelitian adalah eksperimen semu dengan pola pretes-postes. Hasil analisis data pretes dan postes yang diuji melalui analisis anakova menunjukkan adanya perbedaan hasil belajar kognitif siswa pada kelas eksperimen dan siswa pada kelas konvensional. Rerata terkoreksi hasil belajar kognitif siswa pada kelas eksperimen sebesar 69.032 sedangkan siswa pada kelas konvensional sebesar 62.078. Hal tersebut berarti bahwa pencapaian hasil belajar kognitif siswa dengan model PBL berbasis TIK secara signifikan lebih tinggi dibandingkan kelas konvensional. Kata kunci: problem based learning, TIK, hasil belajar kognitif